Encounters, in Spite of All. Samuel Beckett and Paul Celan (ENTHYMEMA, 2019)
The paper investigates from a literary perspective the question of the ‘missed encounter’ between two crucial authors of 20th century: Samuel Beckett and Paul Celan. Although both living in Paris for the most part of their adult life, sharing acquaintances and friendships, Beckett and Celan never met in person. A last chance presented in March 1970, as the poet and translator Franz Wurm, a mutual friend, invited Celan to come along and meet Beckett. The meeting never took place; few weeks thereafter, Celan drowned unobserved in the Seine. In this paper, I propose a retrospective reading of the ‘missed’, or ‘failed’ encounter between Beckett and Celan within a psychoanalytic framework. I will analyse it as a negative event, re-elaborating thus an expression used by André Green in his interpretation of Henry James’ The Beast in the Jungle (1903). What Green calls negative event does not provide a patho-biographical category. On the contrary, it bridges the reverberations of the psychic work on absence with the creative process of writing and the dynamics of sublimation. Shifting the attention from the bare biographical data to the textual dimension of such ‘missed encounter’, I aim to show how the writings of the two authors may be read as an articulation of an après-coup of a non-encounter which, instead of taking place in ‘real life’, opens new margins of representation of an alterity within the ‘life of writing’. As such, writing becomes—between poetry and psychoanalysis—that ‘thirdness’ harbouring the very possibility of an encounter beyond phenomenological categories, bearing testimony for an unknown transgenerational reader.